2016
DOI: 10.1126/science.aad4228
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Global assessment of arbuscular mycorrhizal fungus diversity reveals very low endemism”

Abstract: Davison et al. (Reports, 28 August 2015, p. 970) claim that virtual taxa of Glomeromycota show little endemism and that endemism that exists is similar to the levels seen in plant families. We show that this is likely due to the conservative species definition rather than to any ecological pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 11 publications
0
54
0
Order By: Relevance
“…We anticipate that molecular markers vary substantially in taxonomic resolution and that optimal thresholds for species delimitation may differ across fungal phyla. In particular, SSU and LSU are often estimated to have coarser taxonomic resolution than other fungal barcoding markers (Lindahl et al ., ; Bruns & Taylor, ; but see Thiéry et al ., ). However, our results do not support systematic deviation of network structure among studies based on SSU, LSU, ITS or culture morphology.…”
Section: Discussionmentioning
confidence: 99%
“…We anticipate that molecular markers vary substantially in taxonomic resolution and that optimal thresholds for species delimitation may differ across fungal phyla. In particular, SSU and LSU are often estimated to have coarser taxonomic resolution than other fungal barcoding markers (Lindahl et al ., ; Bruns & Taylor, ; but see Thiéry et al ., ). However, our results do not support systematic deviation of network structure among studies based on SSU, LSU, ITS or culture morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, dispersal limitation seems to have a crucial role in producing the patterns of fungal diversity and community structure that are observed across a range of spatial (see the figure, solid lines (or, where speculative, dashed lines)) and temporal scales (see the figure, y-axis). Evolution of unique bio-geographical assemblages [48][49][50][51] Limited gene flow leads to population differentiation 47,52 Introduction of invasive species disrupts local communities 109 Dispersal limitation may affect species richness and colonization rate for isolated habitats 37 Priority effects increase spatial heterogeneity of assemblages 66,67,68 Dispersal traits influence community assembly 37 Dispersal distance of most spores 37,114,116 Nature Reviews | Microbiology…”
Section: Box 3 | Spore Dispersalmentioning
confidence: 99%
“…For example, a recently published study that shows global cosmopolitanism for arbuscular mycorrhizal fungi 47 may be an artefact of using a highly conserved gene locus. To illustrate the potential of a highly conserved gene locus to produce such an artefact, consider the effect of using an analogous locus to define mammalian species: such a classification would combine humans, most placental mammals and some marsupials into a single species 48 . Similarly, the litter saprotroph Thelonectria discophora in the Ascomycota, was, until recently, thought to be a classic example of a cosmopolitan species, being present on every continent except Antarctica.…”
Section: Beringiamentioning
confidence: 99%
“…They concluded that orchid distribution was not limited by OMFs at geographic scales, but it could be locally limited. Some of the apparent lack of limitation and wide geographic distribution of OMFs, as well as many arbuscular and ectomycorrhizal fungi, may be a result of lumping fungi into ‘species’ based on inappropriate DNA sequence similarity (Bruns & Taylor, ). The goal of this review is to expand beyond the conclusions of McCormick and Jacquemyn by examining more recent research results and the evidence for the ways in which OMFs can be limiting at local scales, including evidence for the effects of OMFs abundance and identity.…”
Section: Orchid Mycorrhizaementioning
confidence: 99%